2012
DOI: 10.1680/macr.10.00157
|View full text |Cite
|
Sign up to set email alerts
|

Retrofitting of reinforced concrete beams in shear using external prestressing technique

Abstract: Retrofitting of existing concrete structures has become an important issue nowadays in the construction industry.There are many causes for repair and/or strengthening, but normally change of use, increased demands on the structure, errors in the design or/and construction phase or accidents are responsible. Many methods to repair and/or strengthen concrete structures exist, such as concrete overlays, shotcrete, external prestressing using cables and so on. This research presents laboratory tests of nine reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…After diagonal cracking, the shear is transferred to the shear reinforcement until the critical diagonal crack becomes so large that shear failure occurs. This behaviour was also observed for deep beams and slabs [3,4,[8][9][10].…”
Section: Adhikary Andsupporting
confidence: 64%
“…After diagonal cracking, the shear is transferred to the shear reinforcement until the critical diagonal crack becomes so large that shear failure occurs. This behaviour was also observed for deep beams and slabs [3,4,[8][9][10].…”
Section: Adhikary Andsupporting
confidence: 64%
“…The results concluded that the surge in the effective strength led to the increase in the ultimate load effective prestressing [8]. The case of tendon profile demonstrated that the final load increased for the selected structure with different draped tendons when compared to the draped tendon profiles [9]. This analysis utilized finite element to analyze the parameters of continual concrete beam prestressed with external ligament while our research utilized the ConsiceBeam software investigate the effectiveness of external prestressing in rehabilitating RC beams.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 10 indicates the required dimensions and the free boody diagram of the proposed technique. The following proposed equation (Eqn 7) gives more precise prediction of the ultimate tendon stress for the case of proposed hybrid strengthening technique as illustrated in table (7) which reported the output of the proposed equation is compared with the experimental result. f c = 0.8 concrete compressive strength of the member α, coefficient of preloading level, α = 1 + 0.1 P L (9) where P L is the preloading level.…”
Section: Proposed Tendon Stress Prediction Modelmentioning
confidence: 99%
“…This type of prestressing can be applied to both new and existing structures that need to be strengthened due to several reasons such as: changes in use, deficiencies in design or construction phase and structural degradation. At present, the application of external prestressing to deteriorated, overloaded or aging existing structural members using unbonded tendons is proving to be a very effective and promising in strengthening structural elements or systems [5,6,7,8,9,10]. Even in well designed concrete members cracking is the main cause of failure as it can lead to loss of structural integrity allowing partial or total collapse mechanisms to occur.…”
Section: Introductionmentioning
confidence: 99%